THE TEACHING OF CRIMINAL LAW IN LEGAL COURSES: THE NEED FOR HUMANIST TRAINING AND RESPONSIBLE CRITICAL CONSCIOUSNES (Revista Direito em Debate, 2020)
It deals with the analysis of legal education and reflection on its distancing from the Brazilian reality and shows how the discipline of criminal law can contribute to a humanistic formation with a responsible critical conscience, capable of moving beyond dogmatism and the comfort zone of penalism technical and legal and create new paths for the realization of rights. The graduates of Law courses, for the most part, replicate in practice their studies, with a mere reaffirmation of the law, reproducing a decontextualized, dogmatic and unidisciplinary knowledge. The hypothetical-deductive method is used. The collection and analysis of the bibliographic material was developed with the purpose of substantiating the knowledge already consolidated on the subject, as well as presenting the controversial points on the subject. It concludes that it is necessary to apply to the disciplines of Criminal Law, Criminology, including Critical Criminology, which is decisive in relation to the form of application and interpretation of criminal legal control and Criminal Policy, in a conjugated way, putting in practice the prediction of the current National Curricular Guidelines for Law courses (Resolution no. 9/2004), of the National Education Council (CNE).
Keywords: Legal Education. Critical Criminology. Humanistic training.